2016
DOI: 10.1038/srep32222
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide exposure and risk of Alzheimer’s disease: a systematic review and meta-analysis

Abstract: Evidence suggests that lifelong cumulative exposure to pesticides may generate lasting toxic effects on the central nervous system and contribute to the development of Alzheimer’s disease (AD). A number of reports indicate a potential association between long-term/low-dose pesticide exposure and AD, but the results are inconsistent. Therefore, we conducted a meta-analysis to clarify this association. Relevant studies were identified according to inclusion criteria. Summary odds ratios (ORs) were calculated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
105
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(113 citation statements)
references
References 46 publications
2
105
0
6
Order By: Relevance
“…34 Moreover, adverse health outcome may develop after a substantial delay, as has been suggested for early-life exposures to certain pesticides that may trigger subsequent development of degenerative nervous system disease at a younger age than anticipated. 35 Similar observations refer to cancer development. For example, rats treated with aspartame at low doses from pre-natal life have been reported to develop higher incidence of malignant tumours compared with rats first treated at maturity.…”
Section: Vulnerable Developmentmentioning
confidence: 64%
See 1 more Smart Citation
“…34 Moreover, adverse health outcome may develop after a substantial delay, as has been suggested for early-life exposures to certain pesticides that may trigger subsequent development of degenerative nervous system disease at a younger age than anticipated. 35 Similar observations refer to cancer development. For example, rats treated with aspartame at low doses from pre-natal life have been reported to develop higher incidence of malignant tumours compared with rats first treated at maturity.…”
Section: Vulnerable Developmentmentioning
confidence: 64%
“…Puberty also may represent an additional vulnerable time window . Moreover, adverse health outcome may develop after a substantial delay, as has been suggested for early‐life exposures to certain pesticides that may trigger subsequent development of degenerative nervous system disease at a younger age than anticipated . Similar observations refer to cancer development.…”
Section: Vulnerable Developmentmentioning
confidence: 89%
“…Systematic reviews and meta-analyses of reported epidemiological links have been presented [38,51,52]. A meta-analysis of past reports in 2016 (which included 3 cohort studies and 4 case-control studies) has concluded that pesticide exposure is positively associated with AD (OR, 95% CI: 1.34, 1.08-1.67) [51].…”
Section: Epidemiological Links Between Pesticide Exposure and Alzheimmentioning
confidence: 99%
“…Systematic reviews and meta-analyses of reported epidemiological links have been presented [38,51,52]. A meta-analysis of past reports in 2016 (which included 3 cohort studies and 4 case-control studies) has concluded that pesticide exposure is positively associated with AD (OR, 95% CI: 1.34, 1.08-1.67) [51]. Another, more recent meta-analysis in 2019 of 19 studies of occupational exposures to multiple agents on neurodegenerative diseases (13 on AD) has also concluded that occupational exposure to pesticides increased the risk of AD (weighted relative risk (RR), 95% CI: 1.50, 0.98-2.29) [52].…”
Section: Epidemiological Links Between Pesticide Exposure and Alzheimmentioning
confidence: 99%
“…Background There is increasing evidence suggesting the role of environmental factors in the development of dementia or Alzheimer's disease (AD) [1][2][3]. One systematic review including a meta-analysis reported a positive association between pesticide exposure and AD [4]. Since polychlorinated biphenyls (PCBs) and organochlorine (OCs) pesticides, also known as persistent OC compounds, were reported to induce cognitive, motor and behavioral deficits in animal models through a number of potential modes of action [5,6], growing interest in ascertaining their relationship with cognitive impairment [7][8][9][10][11], allcause dementia and AD [12][13][14][15] and Lewy pathology [16] has been mostly noticed in recent years.…”
Section: Abstract: Alzheimer's Disease Dementia Cognitive Declinementioning
confidence: 99%